Approach to difficult urethral catheterizations in male patients during the Covid-19 pandemic - Koçakgöl, Hüseyin (Journal of Surgery and Medicine, 2021)
Background/Aim: Difficult urethral catheterization (DUC) is a frequent urological emergency in daily practice. Anticoagulant and antiaggregant drugs, included in the treatment protocols for COVID-19, tend to increase the risk of possible complications of alternative interventions, such as cystoscopy and suprapubic percutaneous cystostomy. Therefore, a less invasive method is needed in patients with DUC. This study aims to evaluate the results of Foley catheter insertion and urethral dilatation over a hydrophilic guidewire in patients with DUC. Methods: A total of 23 male patients who visited the urology outpatient clinic or were referred due to urinary retention or inability to place a Foley catheter in the last 8 months were included in this case series. The patient charts were evaluated retrospectively. After the hydrophilic guidewire, blindly advanced from the urethral meatus under sterile conditions, reached the bladder, a Foley catheter was placed over the guidewire. In cases of urethral stricture, dilatation was performed over the guidewire with the help of hydrophilic S-Curve dilators, and a Foley catheter of suitable diameter was placed. Results: A Foley catheter was successfully placed in 22 out of 23 patients. Urethral dilatation was performed in 13 patients due to urethral stricture, and a transurethral Foley catheter was placed in the other 10 patients without the need for dilatation. Although most of our patients (17 of 23 patients) were receiving anticoagulant or antiaggregant treatment during the procedure, no significant hemorrhagic complications occurred. A Foley catheter could not be placed in one patient with this technique; a percutaneous cystostomy catheter was placed instead. Conclusion: The results of this study, conducted during the COVID-19 pandemic, show that our technique is safe and successful. We believe that our technique will be useful in preventing additional surgical interventions due to complications, especially during this pandemic.